Feeding habits of Sotalia fluviatilis in the Amazonian Estuary - Beltrán-Pedreros, Sandra; Araújo Pantoja, Tatyanna Mariucha de (Acta Scientiarum - Biological Sciences, 2006)
In this paper we present an analysis of the fifty S.fluviatilis feeding habits in the Amazonian Estuary. Animals were bycaught by the artisanal fishing fleet between 1996 and 2001. Feeding habits were analyzed by prey occurrence frequency (%F) and number percentage and stomachs contents preys similarity between marine and freshwater fish species present in the Amazonian Estuary. Thirteen fish species were identified (%F= 86.6), the most significant families were Sciaenidae (32%), Trichiuridae (26%) e Ariidae (16%), and four crustaceans species (%F=26). S. fluviatilis feeding habits did not differ by gender and in general, calves had higher prey diversity than juveniles and adults. The similarity was high (0.89) between estuarine S. fluviatilis feeding habits and the fishes species present in the Amazonian Estuary when the environment is mostly marine.
Keywords: Animals Experiment; Biodiversity; Controlled Study; Crustacea; Dolphin; Estuary; Feeding Behavior; Female; Fishing; Freshwater Fish; Male; Nonhuman; Prey; Stomach Content; Animalsia; Ariidae; Crustacea; Pisces; Sciaenidae; Sotalia Fluviatilis; Trichiuridae